2018
DOI: 10.1103/physrevb.97.134513
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Fulde-Ferrell-Larkin-Ovchinnikov states in atomic Fermi gases in three and two dimensions

Abstract: The exotic Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) states have been actively searched for experimentally since the mean-field based FFLO theories were put forward half a century ago. Here we investigate the stability of FFLO states against unavoidable pairing fluctuations, and conclude that FFLO superfluids cannot exist due to their intrinsic instability in three and two dimensions. This explains their absence in experimental observations in both condensed matter systems and the most recent, more promising ult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 115 publications
1
22
0
Order By: Relevance
“…While the FFLO mean-field solution usually exists at low T, when pairing fluctuations, which usually lead to the formation of a pseudogap, are taken into account, the mean-field FFLO states become unstable, in the absence of extrinsic symmetry breaking factors such as spatial anisotropy and lattices, as found in ref. [15]. Similar results were found by others as well.…”
Section: Further Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While the FFLO mean-field solution usually exists at low T, when pairing fluctuations, which usually lead to the formation of a pseudogap, are taken into account, the mean-field FFLO states become unstable, in the absence of extrinsic symmetry breaking factors such as spatial anisotropy and lattices, as found in ref. [15]. Similar results were found by others as well.…”
Section: Further Discussionsupporting
confidence: 91%
“…While a stable FFLO state may exist in an anisotropic system [8,9] or in a lattice, [9][10][11] especially in a low dimensions, [12][13][14] however, it has been shown that the FFLO states are intrinsically unstable in clean homogeneous 3D and 2D continuum systems. [15] Instead, noncondensed pairing with the lowest pair energy at finite momenta is expected, which may lead to exotic ground states. Thus it is important to find the true solution where the unstable mean-field FFLO solutions exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another question concerns the influence of the competing FFLO phase (characterized by nonzero ordering wavevector) on the excitation spectra. Even though theoretical results [61][62][63][64][65] suggest that, in case of the neutral Fermi superfluids, these pair density wave states are unstable at T > 0, they are presumably still present as ground states. We finally note the interesting question concerning the impact of imbalance on damping of the amplitude mode, whose existence was recently experimentally established.…”
Section: Discussionmentioning
confidence: 98%
“…We finally point out that in a beyond-mean-field picture, the FFLO-type phases are suspected [64][65][66] to be marginally unstable to fluctuation effects in dimensionality d = 3 at T > 0 (but not at T = 0). This would imply that, at least for infinite and homogeneous systems, the quantum Lifshitz point should always occur in the phase diagram if there is a phase transition between the FFLO-type and uniform superfluid phases at T = 0.…”
Section: A Gradient Expansion and The Quantum Lifshitz Pointmentioning
confidence: 88%